KAJIAN DAMPAK PERUBAHAN IKLIM GLOBAL TERHADAP KARAKTERISTIK HUJAN DI WILAYAH JABODETABEK - , KUMARA DAMARLANTU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Flooding is an annual problem that occurred in Jakarta. Flooding always come during the rainy season. Rain includes weather phenomena influenced by climate change which lately is becoming a hot discussion in the international. Extreme change weather, storms, rising temperatures, and rising sea level considered as the impact of the worldâs climate change. According to the World Bank, the adverse effects of flooding in Jakarta are the economic and social stability. To determine the effectiveness of policies in the areas of Jakarta, the need for prediction, in order to obtain real data on how much influence the characteristics of the phenomenon of climate change on rainfall that occurred. Simulated rainfall prediction was conducted using the Statistical Automated Downscalling (ASD). ASD program is run with Matlab software. Input using rainfall data as predictands. Global climate data from global atmospheric reanalysis issued NCEP (National Centers for Environmental Prediction) data and prediction of the global atmospheric GCM (General Circulation Models) as predictors. Rain is predicted to belong HadCM3 climate scenarios, and scenarios of greenhouse gases following the SRES scenario A2 ( with environmental policy) and B2 (no environmental policy). Predictions made in 3 periods of the 2020s period (2011-2040), 2050s period (2041-2070) , and 2080s period (2071-2099). Analysis of rainfall prediction provides information that the changes pattern of characteristics are vary. The increase also occurs more frequently in the wet than in the dry months. In addition, there is the possibility of a shift in the rainy season. Potential flooding in the Jakarta area will probably come early, but can be suppressed using environmental conservation efforts.